Televisão e deficiência visual: o sonoro na produção de imagens mentais - Neves, Camila Portella (2012)
The object of this work is the visuality formed by the blind people when watching television. The objective of this research is to analyze the sound as a resource to forming mental images to understand and generate knowledge of the world passed through what is on television for the visually impaired. As specific objectives, intends to examine the TV as a way of understanding the world and as a means of information for the visually impaired, also noting the extent to which the sound replaces the image in the apprehension of which is transmitted by TV. It also aims to analyze to what extent the visually impaired can reproduce the world through sound and identify what kind of visuality is produced by the visually impaired while watching TV. In TV programming, there is a perfect union of image and sound, playing a central role in Brazil in the knowledge of individuals. However, this unique feature in the union of the TV picture and sound, while it can reach a higher percentage of fans, also limits access to those who do not have the feature imagery. This is the case of the blind, which receive only the character of the sound that is transmitted. In view of this, this research has the following problem: being the eyes a sense of excellence in the mass mediation of images, how the blind people experience mental images while watching television? It starts with the hypothesis that the mental visuality produced by blind people can lead to understanding what is televised. In such case, it is believed that through the perception and discrimination of sound, the blind people can produce mental images. Another hypothesis is that, through a polisensitive discrimination, the visually impaired are developing another kind of learning supported by a system of analogies. In view of this, the fourth hypothesis is that through the sound the blind people can elaborate images by expansion of cognitive operations. It is a qualitative research which uses the abductive-inductive method, and for its development, we intend to conduct an empirical illustration with people with visual impairments. For the development of this dissertation will be discussed about the representation as a sign (Charles Sanders Peirce); about the mental representations produced by the blind (Antonio Damasio), entering the enclosure of Cognitive Sciences; on perception (Lucia Santaella), and how the sound is seen by the blind people as a way of thinking in the absence of the image, passing in front of it, by the concept of compensation (Semionovitch Lev Vygotsky)